P72 NeVa™️ thrombectomy device (NvTD): initial experience in a regional argentinian stroke care center. (29th August 2022) - Petra, F; Caballero, G; Graña, M; Fernandez, C; Alvarado, L; Gonzalez, M; Nazar, F; Horvath, F; Galiana, G; Genco, J; Parra, L
Abstract : Background: The (NvTD) (Vesalio LLC, Nashville, USA) had shown high recanalization rates in LVO thrombectomy, either in animal, in-vitro, and in previously available clinical studies. A new architecture, called, ¨Drop Zone technology¨ (closed distal tip, strong expansive radial force, with different clot entrapment areas), would might show high First Pass Effect rates. Aim: To assess the safety and efficacy of this new tech retriever. Methods: Between November 2019 and April 2022, 52 patients were prospectively analyzed after going under NvTD as first-line of treatment strategy in LVO strokes. First-pass and final recanalization, 90-day functional outcome, complications, and complication were reported. Results: Between November 2019 and April 2022, 52 patient (24 female, 28 male, 68 yo average, 42–84 yo age interval) patients were enrolled. At admission, median NIHSS was 23, 3, and median ASPECT score was 8, 2. The median time from groin to successful recanalization was 34 min (interquartile range (IQR): 13–56). First-pass recanalization rates were 58, 8% (mTICI) 2b/3) and 34.9% (mTICI 2c/3). Final successful recanalization rate was 93.7% (TICI 2b/3). Favorable mRS 0–2 was 61, 5% in the "first-pass" subgroup and 57, 6% in the hole population. The median passes to final recanalization score was 1 (IQR 1–2). Embolization into new territory was seen in 1.9%. Symptomatic hemorrhage was observed in 3 patients (5, 76%). Conclusions: The NvTD showed high First Pass and overall recanalization rates. Even though a safety profile was observed, further investigation regarding this item are needed. References: Ribo M, Requena M, Macho J, et al . Mechanical thrombectomy with a novel stent retriever with multifunctional zones: initial clinical experience with the Neva™ thrombectomy device. J Neuroradiol 2020;47 :301–305. Goyal M, Menon BK, Van Zwam WH, et al . Hermes collaborators. Endovascular thrombectomy after large-vessel ischaemic stroke: a meta-analysis of individual patient data from five randomised trials. Lancet 2016;387 :1723–1731. Do you have any conflict of interest to declare? : No